2016
DOI: 10.2147/ppa.s99730
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of color and lip position for facial attractiveness by laypersons and orthodontists

Abstract: BackgroundPrevious studies have reported some evaluation methods about profiles, but so far, they have no consistent agreement on the esthetic profiles of color images. Thus, the aim of this study was to determine whether the judges have different preferences about the color of the photograph and lip position for esthetic profiles when comparing a Chinese boy and girl.MethodsThe photographic records of a Chinese boy and girl with a good balanced profile were randomly selected. The images of the patients’ profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…19,23 This method has generated a robust set of attractiveness data, allowing for a highly powered statistical analysis compared with all previous studies on focus group evaluation of lip aesthetics. 4,[24][25][26][27] Several goals exist for lip augmentation, including improving lip fullness, restoring volume in age-associated atrophy, and providing a more distinct vermillion border and philtrum. 28 General guidelines offer the practitioner options for creating an ideal aesthetic but are often based on subjective analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,23 This method has generated a robust set of attractiveness data, allowing for a highly powered statistical analysis compared with all previous studies on focus group evaluation of lip aesthetics. 4,[24][25][26][27] Several goals exist for lip augmentation, including improving lip fullness, restoring volume in age-associated atrophy, and providing a more distinct vermillion border and philtrum. 28 General guidelines offer the practitioner options for creating an ideal aesthetic but are often based on subjective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our robust virtual model for ranking facial attractiveness used a combined traditional and internet-based focus group to perform aesthetic analysis . This method has generated a robust set of attractiveness data, allowing for a highly powered statistical analysis compared with all previous studies on focus group evaluation of lip aesthetics …”
Section: Discussionmentioning
confidence: 99%
“…In this study, 4 average faces’ profiles all met the E line standard created by Ricketts. This result was inconsistency with some other researches, such as Qingjuan Shi, who reported that Chinese prefer the concave facial profile; 34 Macias, GA, who concluded that in young Spanish population, attractive females tended to present a convex profile than males and all attractive individuals had lips inside the Ricketts’ E line; 35 Ioi, H et al, who found a slightly convex profile was more acceptable than a concave profile in Japan. 36 …”
Section: Discussionmentioning
confidence: 60%
“…Poređenjem bočnih profila lica različitih rasa, kod bele rase je primećeno znatnije izbočenje donje usne kod ženskog pola nego kod osoba muškog pola, a zajedno sa tim i mnogo veće vrednosti koje se odnose na udaljenost od referentnih linija u odnosu na žutu rasu, što nam ukazuje da pripadnici žute rase imaju konkavniji profil lica (8,9). Zatim, kada se osvrnemo na pripadnike crne rase, možemo uočiti prominentniju i gornju i donju usnu u poređenju sa belcima (10) Primarni cilj ove studije bio je da se ustanovi u kojoj meri se profili lica grupe mladih odraslih ispitanika približavaju idealnom profilu i propisanim referentnim vrednostima iz literature.…”
Section: Uvodunclassified
“…Navodi iz literature o pripadnicima žute rase sugerišu da Kinezi najčešće imaju konkavan profil lica, a naravno, kako u svemu postoje izuzeci, tako i ovde određeni procenat stanovništva koji nema konkavan profil obično biva podvrgnut operacijama kojima modifikuje izgled lica, pa samim tim i profila (9). Rezultati ukazuju da je rastojanje gornje i donje usne u odnosu na Riketsovu liniju bilo u granicama normale (0,44/0,15 mm (m) i 0,65/0,23 mm (ž)).…”
Section: Diskusijaunclassified